Analisis Sistem Layanan Psikologi di Pendidikan Sekolah Dasar - Erlyani Fachrosi (Universitas HKBP Nommensen, 2020)
One of the educational foundations with the concept of active, fun learning school by using nature as a direct medium for learning. One psychology service unit (Unit Pelayan Psikologi/UPP) is used as a means of communicating cooperation between counselor and client. The problem that occurs is the UPP that is not utilized optimally by the teaching department in schools. Complaints were not working properly and there was a lack of coordination regarding the follow-up of the handling results. The lack of involvement of teachers as educators with unit counselors causes delays in handling students who experience academic and psychological problems. The purpose of this study was to carry out SWOT-based assessment and analysis to develop appropriate recommendations to evaluate and develop adequate programs. Research methods carried out with a system-based qualitative approach. Data collection was carried out with interviews with a number of parties such as CEOs, vice principals in the fields of curriculum and student affairs, psychology service unit staff, and classroom teachers. In addition, school physical observations, FGD observations, and class board activities. Another analysis of documents such as secondary data from case documentation, teacher and coordinator jobdesc, and previous system analysis. The results show the lack of competency in UPP and the referral system that has not been well coordinated.